El Excentrico, 1967-12-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
December 20, 1967 [20 de diciembre de 1967]. No volume or issue number. Cover has a Christmas Greeting Card with headshot of entrepreneur Hank Coca. The headline reads "Hank Coca's Furniture Discount House and Staff."